High-Performance Supported Ru Catalysts for the Aqueous-Phase Hydrogenation of Levulinic Acid to γ-Valerolactone - Leguizamón Aparicio, María Silvia del Valle (2024)
γ-Valerolactone (GVL) can be obtained by efficient hydrogenationof levulinic acid using ruthenium-based catalysts in anaqueous medium. This paper reports an in-depth study on theactivity and selectivity of Ru catalysts supported on zirconiaalumina,focusing on the effect of Ru concentration (0.5, 1.5 and3 wt.% of Ru) and the selection of operational reactionvariables. The results showed that the activity strongly dependson the number and oxidation state of the supported rutheniumparticles. The most active catalyst, Ru3/ZA, presented thehighest number of nanometric particles of zerovalent Ru andthe highest number of acid sites. This catalyst gave ca. 100%selectivity towards GVL, at high conversion of levulinic acid(over 99%) under the best operating conditions evaluated(120 °C, 3 MPa H2 pressure, 1 h of reaction, and 0.1 g of catalyst).In addition, this catalyst kept high levels of conversion andselectivity after successive reuse cycles.